Exploring the Influences of a Leadership Certificate on Career Readiness - Kathy L. Guthrie; Vivechkanand Chunoo; Sally R. Watkins (Ali Khorsandi Taskoh, 2022)
Embracing student engagement through leadership learning in higher education and focusing on identified competencies prepares students for future careers. This study explored the influence of leadership certificate participation on workforce preparedness by specifically investigating, "In which ways do leadership certificate alumni attribute progress toward their academic and career goals to their participation in their certificate?" This qualitative study used semi-structure interviews to get a better sense of learning outcomes of an academic leadership certificate program. Two major findings emerged from participant responses to how the certificate program informed their employment reparation. These two findings include inspiring creativity in themselves and others, as well as setting personal and professional priorities.